Dampak Kantin Kejujuran Sebagai Media Pembelajaran Akhlak Terhadap Akhlak Jujur Siswa di SMK N 01 Koto Balingka Kabupaten Pasaman Barat - Fauza Ulyani; Arifmiboy (Program Studi Akuntansi IKOPIN, 2022)
This research is based on the background as it is known that canteen guards at SMK N 01 Koto Balingka often complain about students' cheating actions when shopping. In practice, students always apply the system of eating 3, paying 2, claiming 1 so that students' honesty is not applied when shopping in the canteen, so the vice head of student affairs proposes to establish an honesty canteen with the aim that students' honest attitudes are trained and accustomed to being honest. This research was carried out with the aim of knowing the management of the honesty canteen at SMK N 01 Koto Balingka, To find out how the honesty canteen is used as a moral learning medium, To find out how the impact of the honesty canteen on the morals of students in SMK N 01 Koto Balingka. This research uses a qualitative descriptive approach with the type of case study research. This research collects data by interview and documentation method. Sources of data used to collect data in the form of school data and interviews. Data analysis starts from data reduction, data presentation, and drawing conclusions. The results showed that the management of the honesty canteen at SMK N 01 Koto Balingka was initially planning to form an honesty canteen, then preparing the canteen's willingness to stand up and finally carrying out the honesty canteen process. honesty. The honesty canteen is a canteen provided by the school without any sellers or guards, students transact themselves in the canteen and take whatever they need and put their money in the payment box provided, To find out how the impact of the honesty canteen on the morals of students at SMK N 01 koto This balingka is that with the existence of an honesty canteen, it can provide positive education and benefits for students. Such as training students' honesty because they are required to pay according to the price listed, so that it is also useful for fostering an anti-corruption spirit in students and changing bad traits such as stealing, because if someone else finds out then they are advised not to steal again, so the thief will not repeat his actions again.